Impact of GST on Small and Medium Enterprises (SMES) owned by Women (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The Goods and Services Tax (GST) implemented in India has significantly altered the tax landscape for businesses, including Small and Medium Enterprises (SMEs). This paper examines the impact of GST on SMEs owned by women, utilizing secondary data sources to understand the implications of GST on business operations, financial performance, and overall growth. By analyzing existing literature, government reports, and industry surveys, this study aims to provide insights into how GST has affected women entrepreneurs and their businesses. The findings suggest that while GST has introduced efficiencies and simplifications, there are also challenges such as increased compliance costs and cash flow issues that disproportionately affect women-owned SMEs.